Critical but co-operative: Netizens evaluating journalists in social media - Noppari,Elina (2014)
This article looks into the relationship between professional journalists and active Web users in the sphere of social media1. Our exploration into journalists social media participation is approached through two clashes of cultures between the online context and the world of journalism, namely anonymity and transparency. The research, which is based on interviews with journalists and experts and a survey to the web users, permits the conclusion that the relation between journalists and public is fraught with suspicion and conflict. Newsrooms should be more open as regards journalistic practices, but frequently they are not accessible to the public.